2022
DOI: 10.3389/fphys.2022.981750
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of dietary fish meal with Clostridium autoethanogenum meal on growth performance, intestinal amino acids transporters, protein metabolism and hepatic lipid metabolism of juvenile turbot (Scophthalmus maximus L.)

Abstract: Clostridium autoethanogenum meal (CAM) is a novel single-cell protein, which is produced from bacteria using carbon monoxide (CO) as sole carbon source. To evaluate the efficiency of CAM as an alternative for dietary fish meal, a 56-days growth experiment was performed on juvenile turbot (Scophthalmus maximus L.) with initial average weight of 9.13 ± 0.02 g. Six iso-nitrogenous (crude protein, 51.0%) and iso-lipidic (crude lipid, 11.5%) diets were formulated with 0%, 15%, 30%, 45%, 60% and 80% dietary fish mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 56 publications
(72 reference statements)
1
5
1
Order By: Relevance
“…The present work together with previous work on juvenile turbot (Zheng et al 2022) and M. salmoides (Ma et al 2022) proved that CAP disturbed the sh lipid metabolisms. Dietary CAP decreased the plasma triglyceride and cholesterol levels in all three works.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The present work together with previous work on juvenile turbot (Zheng et al 2022) and M. salmoides (Ma et al 2022) proved that CAP disturbed the sh lipid metabolisms. Dietary CAP decreased the plasma triglyceride and cholesterol levels in all three works.…”
Section: Discussionsupporting
confidence: 84%
“…In turbot with body weight of 9.13 g, CAP was proved to replace 45% of shmeal protein (Zheng et al 2022). Researches on L. crocea and M. salmoides showed that sh size is one of the key factors decided the optimal dietary level of CAP within the same sh species.…”
Section: Introductionmentioning
confidence: 99%
“…As a type of singlecell protein (SCP), CAP has pleasant quality of high protein content and balanced profile of amino acids, showing great potential to replace fish meal. The studies on largemouth bass (Micropterus salmoides) (CAP replacement level ≤ 43%) and juvenile turbot (Scophthalmus maximus L.) (CAP replacement level ≤ 45%) suggested that an appropriate level of CAP replacing fish meal did not have a significant negative effect on growth performance [4,5]. However, fish growth performance was compromised by a high level of CAP replacing fish meal in diets.…”
Section: Introductionmentioning
confidence: 99%
“…To date, extensive studies have been conducted on large yellow croaker in the nutritional requirements and replacement of fish meal [24][25][26]. Based on the research on carnivorous fish including largemouth bass [4,27], turbot [5], and large yellow croaker [7], we supposed that 45% may be a high level of CAP replacement. To make CAP more widely applied, growth performance, intestinal digestive enzyme activity, antioxidant capacity, and inflammation-related gene expression were evaluated in large yellow croaker fed with different levels of tributyrin supplementation in a high-CAP diet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation